Effects of postoperative physical exercise rehabilitation on cardiorespiratory fitness, functional capacity and quality of life in patients with colorectal, breast, and prostate cancer – a systematic review and meta-analysis - Mailin Beyer; Christian Bischoff; Johannes Lässing; Ines Gockel; Roberto Falz (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The reduced cardiorespiratory fitness (CRF) and functional capacity following surgical procedures and during cancer treatments is a major risk factor for morbidity and mortality among patients with cancer. We aimed to assess the impact of endurance and combined resistance exercise interventions during the postoperative rehabilitation period for patients with colorectal, breast, and prostate cancer. Methods A systematic search was conducted in MEDLINE Pubmed, Web of Science, and Cochrane Library until October 2023 for randomized controlled trials that assessed exercise interventions (aerobic/endurance; resistance or combined training) on postoperative patients with cancer. The trials evaluated the change in oxygen uptake (VO2max), six-minute walking distance (6MWD), quality of life (QoL), and fatigue. Results Twelve studies, including 1298 patients, were part of this systematic review, and ten studies were included in the meta-analysis. Postoperative exercise interventions led to improvements in CRF and functional capacity (VO2max: MD 1.46 ml/kg/min; 95%-CI 0.33, 2.58; p  = 0.01; 6MWD: MD 63.47 m; 95%-CI 28.18, 98.76; p = 0.0004, respectively) as well as QoL (0.91; 95%-CI 0.06, 1.76; p = 0.04). The quality of evidence was moderate to low. Conclusion Postoperative exercise interventions could effectively improve CRF, functional capacity and QoL as shown in this meta-analysis. However, there is a lack of high-quality trials with a higher number of participants examining the effects of postoperative exercise in patients with colorectal, breast, and prostate cancer. There is an obvious need for long-term, cancer-specific exercise therapies and their evaluation in cancer care.